A pilot randomized controlled trial examining the feasibility of perioperative rehabilitation for inguinal hernia repair surgery - Anna Shologan; Omar Farooq; Geoffrey Bostick; Luciana Macedo; Quentin Durand-Moreau; Meaghan Ray Peters; Douglas P. Gross (PLoS ONE, 2025)
Background Despite the high frequency of inguinal hernia repair (IHR) surgery, there is little research investigating pre- or post-operative exercise and education in this population. Recommendations regarding perioperative physical activity are inconsistent and largely based on clinical opinion. We conducted a pilot randomized controlled trial to examine the feasibility of perioperative rehabilitation for inguinal hernia repair surgery in terms of recruitment rate, assessment, and protocol implementation. Methods Participants were randomized into an intervention group and control group. Descriptive and patient-reported data were collected through online surveys at baseline, post-prehabilitation (prehab), 1-week post-operative (post-op), and 12-week post-op. Eligible participants completed a performance-based modified Short Form Functional Capacity Evaluation conducted by a masked observer at baseline, after 6 weeks of exercise and/or education, and at 12-week post-op. Participants in the intervention group received 6 weeks of exercise and education prior to and then after surgery. The control group received care as usual. Results Thirty-one participants awaiting IHR with a mean age of 49 years were recruited (recruitment rate of 51.7%). Thirty participants were randomized into control (n = 16) and intervention groups (n = 14), while 1 dropped out prior to beginning the study due to being unable to take time off work for assessment. Twenty-four participants completed the final 12-week post-op follow-ups. Twenty-one participants returned to work by the 12-week post-op follow-up. Sixty-seven percent of participants in the intervention group exercised at least 3 times per week post-operatively. One participant in each group experienced exacerbations of hernia symptoms that were unrelated to study activities. Functional testing resulted in minimal symptom exacerbation in either group, but the intervention group reported less pain at 12-week post-op than controls. Conclusion A randomized trial of perioperative rehabilitation for patients undergoing inguinal hernia repair appears feasible, but protocol adjustments are needed to improve recruitment rate, assessment, and participant retention. Trial Registration: This trial is registered with ClinicalTrials.gov Identifier: NCT05069142